Implementación de un algoritmo de aceleración del flujo óptimo de potencia (OPF) basado en aproximaciones lineales. - Velasco Avilés, Kevin Alexander (2023)
In the present research project, an OPF acceleration algorithm based on linear approximations is implemented in the AMPL software. Various electrical systems are addressed, such as 14-bus IEEE, 118-bus IEEE, the Ecuadorian National Interconnection System (SNI), and the IEEE PES 793-bus Power Grid System, which must comply with technical and operational constraints. The approach is based on an algorithm of linear successive approximations (ALS) that starts from the Bus Injection Model (BIM) in the energy flow analysis. Subsequently, this algorithm is applied to the mentioned systems through a convex relaxation modeling, thus transforming the problem into an ALS series, speeding up the calculation process, and obtaining efficient solutions. However, it is essential to take into account the characteristics and limitations of the approach, performing a detailed analysis to evaluate its performance in different scenarios. During the execution, data are collected from generators, busbars, and transmission lines of the power system under study, and these data are essential to establish an adequate model. Solvers such as KNITRO, IPOPT, and CONOPT, which are capable of solving optimization problems, are used. The evaluation and comparison of the obtained results validate the implemented methodology, ensuring that the solutions comply with the technical and operational constraints of the system and provide a satisfactory computational time.